Lightning Talk: The Incredible Shrinking Black Box Model - Schaumont, Patrick (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
A black box model is an assumption on the implementation of a cryptographic primitive to limit the capabilities of the attacker. Black boxes are a useful component in a proof of protocol correctness, but it is not obvious how to securely implement one in hardware. The current state of the art in tamper from open literature shows impressive efficiency and precision in prying open these black boxes. Secure hardware designers are compelled to shrink the black boxes with every new device generation, while making a careful assessment of the need to load, store and handle secrets in hardware.